Reflection on Customer Satisfaction Using the Jaket Application in Terms of Aspects of E-Service Quality, Price, and Brand Awareness - Acai Sudirman; Fitria Halim; Onita Sari Sinaga; Fenny Krisna Marpaung (Target : Jurnal Manajemen Bisnis, 2021)
The need for fast transportation services has caused several businesses to try to create application-based transportation applications according to market demand. To answer this market need, application-based transportation is needed that can implement e-service quality and provides prices following consumer expectations so that it is expected to be able to foster strong brand awareness of the application. The purpose of this study is to analyze the contribution of e-service quality, price, and brand awareness to customer satisfaction. This research was conducted by distributing 180 questionnaires to active users of the Jacket application and only 120 questionnaires that can be used. Tests were carried out with the help of statistical tools in the form of Structural Equation Modeling (SEM) based on Partial Least Square. The results showed that e-service quality has a significant positive effect on customer satisfaction. The results of further research show that price has a positive but not significant effect on customer satisfaction. As for the results of the last study, it was found that brand awareness had a significant positive effect on customer satisfaction.